Guidelines for equipment and staffing of radiotherapy facilities in the European countries: Final results of the ESTRO-HERO survey - COFFEY, MARY (My University, 2014)
Background and purpose In planning to meet evidence based needs for radiotherapy, guidelines for the provision of capital and human resources are central if access, quality and safety are not to be compromised. A component of the ESTRO-HERO (Health Economics in Radiation Oncology) project is to document the current availability and content of guidelines for radiotherapy in Europe. Materials and methods An 84 part questionnaire was distributed to the European countries through their national scientific and professional radiotherapy societies with 30 items relating to the availability of guidelines for equipment and staffing and selected operational issues. Twenty-nine countries provided full or partial evaluable responses. Results The availability of guidelines across Europe is far from uniform. The metrics used for capital and human resources are variable. There seem to have been no major changes in the availability or specifics of guidelines over the ten-year period since the QUARTS study with the exception of the recent expansion of RTT staffing models. Where comparison is possible it appears that staffing for radiation oncologists, medical physicists and particularly RTTs tend to exceed guidelines suggesting developments in clinical radiotherapy are moving faster than guideline updating. Conclusion The efficient provision of safe, high quality radiotherapy services would benefit from the availability of well-structured guidelines for capital and human resources, based on agreed upon metrics, which could be linked to detailed estimates of need.
PUBLISHED
Keywords: Radiotherapy; Guidelines; Infrastructure; Staffing; Europe; Radiotherapy; Guidelines; Infrastructure; Staffing; Europe